Hysteroscopy and retained products of conception: An update - Virginia Foreste; Alessandra Gallo; Alfonso Manzi; Carla Riccardi; Jose Carugno; Attilio Di Spiezio Sardo (Wolters Kluwer Medknow Publications, 2021)
Retained products of conception (RPOC) can occur after early or mid-trimester pregnancy termination and also following vaginal or cesarean delivery. It is frequently associated with continuous vaginal bleeding, pelvic pain, and infection. Late complications include intrauterine adhesions formation and infertility. Conventionally, the management of RPOC has been with blind dilation and suction curettage (D and C); however, hysteroscopic resection of RPOC is a safe and efficient alternative. In this review, we analyze the current available evidence regarding the use of hysteroscopic surgery for the treatment of RPOC comparing outcomes and complications of both traditional curettage and hysteroscopic technique. Data search has been conducted using the following databases MEDLINE, EMBASE, Web of Sciences, Scopus, Clinical Trial. Gov., OVID, and Cochrane Library interrogate all articles related to hysteroscopy and the preserved product of conception, updated through September 2020.